2016
DOI: 10.5306/wjco.v7.i1.122
|View full text |Cite
|
Sign up to set email alerts
|

Targeting metabolism in breast cancer: How far we can go?

Abstract: receptor-2 targeted therapy, marked a new era of breast cancer treatment. However, except for chemotherapy, an efficient drug treatment to improve the overall survival of breast cancer patients is still lacking for triple negative breast cancer. Furthermore, a certain proportion of breast cancer patients present with resistance to drug therapy, making it much more difficult to control the deterioration of the disease. Recently, altered energy metabolism has become one of the hallmarks of cancer, including brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 83 publications
0
51
0
1
Order By: Relevance
“…These lipid metabolites are associated with cell proliferation, cellular membrane synthesis and signaling molecules (4)(5)(6). Some of the dysregulated metabolic enzymes, such as the glucose transporter 1 (GLUT1), hexokinase 2, lactate dehydrogenase A, glutaminase and fatty acid synthase have been demonstrated to be novel therapeutic targets of cancers (7). The metabolomics in serum or plasma will be novel diagnostic approach in clinic (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These lipid metabolites are associated with cell proliferation, cellular membrane synthesis and signaling molecules (4)(5)(6). Some of the dysregulated metabolic enzymes, such as the glucose transporter 1 (GLUT1), hexokinase 2, lactate dehydrogenase A, glutaminase and fatty acid synthase have been demonstrated to be novel therapeutic targets of cancers (7). The metabolomics in serum or plasma will be novel diagnostic approach in clinic (8).…”
Section: Introductionmentioning
confidence: 99%
“…Most breast cells acquire fatty acids from circulation system. However, breast cancer cells synthesize fatty acids for structured lipid synthesis (7). Fatty acid synthase (FAS) is an important enzyme in lipid synthesis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Willmann et al (39), used metabolomic profiling to sub-classify different breast cancer cell lines and differentiate not only between them, but also between the cancer cell lines and a non-cancer breast epithelial cell line as well. Research has shown that elevated glycine and lactate indicate increased metabolic changes due to rapid growth of cancer cells, and hence poorer prognosis (5). …”
Section: Discussionmentioning
confidence: 99%
“…receptors), microenvironment (i.e. hypoxia), and glucose metabolism, and how the downstream expression of metabolites can be used for both early detection of breast cancer as well as targeted drug therapies (57). …”
Section: Introductionmentioning
confidence: 99%
“…According to a review completed by Long and colleagues [19], many studies have shown dysregulation in cellular metabolism may associate with resistance to cancer treatment drugs. Various factors, including insulin, insulin-like growth factor (IGF), and inflammatory cytokines, may link diabetes to breast cancer mortality.…”
Section: Discussionmentioning
confidence: 99%